共同希望语言学院强化班效率分析 - Dewi Verensia Tanery (Faculty of Cultural Sciences, Universitas Sebelas Maret, 2025)
Learning efficiency as an indicator of learning pace. The improvement of students' learning efficiency is a goal cherished by every teacher and highly anticipated by both students and their parents. In the context of universal education, intensive classes provide students an opportunity to review classroom knowledge, revisit unfamiliar or poorly understood concepts, and master and apply them effectively. The Common Hope Language Institute has established